Evaluation of parents' knowledge about the stem cells' importance of primary teeth in Isfahan - Maryam Hajahmadi; Nosrat Nourbakhsh; Azadeh Salehzadeh; Najmeh Akhlaghi; Mehrnaz Safi (Wolters Kluwer Medknow Publications, 2020)
Context: Stem cells (SCs) present in the pulp of primary teeth can be used for the treatment of many diseases as well as regeneration and renovation. This study investigated the parents' awareness of the importance of primary teeth SCs in Isfahan. Aims: The aim of the study was to understand the level of parent's knowledge about primary teeth SCs and the source of their knowledge. Settings and Design: It was a descriptive research that was done in university clinics of Isfahan city. Subjects and Methods: This descriptive-analytic, cross-sectional study was carried out on 384 parents referring to the clinics and dental offices of Isfahan using a self-administered questionnaire. Statistical Analysis Used: Data were analyzed by one-way ANOVA and Pearson's correlation coefficient (α = 0.05). Results: The mean age of the parents was 37.55 years. The mean score of knowledge in the whole sample was 4.85 ± 3.83. The knowledge score was higher in the mothers (5.8 ± 3.91) than in the fathers (4.28 ± 3.54). Spearman's correlation coefficient showed a significant difference between the mean scores of parents' knowledge and the number of children (r = −0.1, P = 0.05), residence (P = 0.001), economic status (r = 0.442, P < 0.001), education (r = 0.556, P < 0.001), job status (P < 0.001), and frequency of dental referrals (r = −0.337, P < 0.001). However, no significant relationship was found between the mean score of knowledge and age (r = −0.7, P = 0.176). Conclusion: Data from this study revealed that parental knowledge about primary stem cells is inadequate.